Overexpression of the Salix matsudana aquaporin gene SmPIP1;3 enhances plant resistance to abiotic stresses - Xu, Xiao; Yin, Peng; Wang, Lei; Lu, Xiaoxiong; Xu, Jichen (Frontiers in Plant Science, 2025)
Plasma membrane intrinsic proteins (PIPs) are involved in plant growth and stress adaptation through their dynamic gating mechanism. Nevertheless, pinpointing the specific roles of individual isoforms remains challenging because of their functional pleiotropy and integrated responses to diverse cues. In this study, we characterized a salt-responsive aquaporin gene, designated SmPIP1;3, isolated from a salt-resistant Salix matsudana variety. Bioinformatics analysis confirmed that it encodes a protein that possesses canonical PIP features with six transmembrane domains, five interhelical loops, and seven serine phosphorylation sites involved in phosphorylation-mediated regulation. The SmPIP1;3 gene was introduced in tobacco plants, and its heterologous expression conferred significant morphological improvements, including taller plant height, larger leaves, longer roots, and increased biomass. Under salt, drought, cold, and heat stresses, transgenic plants showed substantially alleviated membrane damage, as evidenced by weakened Evans blue staining. Consistently, their malondialdehyde contents were 1.48-, 1.47-, 1.57-, and 1.62-fold lower, while relative electrolyte leakage values were 1.56-, 1.35-, 1.53-, and 1.61-fold lower than those of wild-type plants, respectively. SmPIP1;3 orchestrates multi-stress tolerance by sustaining physiological homeostasis and limiting membrane damage. Its performance positions it as a valuable genetic asset for molecular breeding programs.